Short review: Potential impact of delamination cracks on fracture toughness of structural materials - X.C. Arnoult; M. Ružicková; K. Kunzová; A. Materna (Fracture and Structural Integrity, 2015)
The current energy policy envisages extended lifetime for the current nuclear power plants (GEN II NPP). This policy imposes a large research effort to understand the ageing of power plant components. In this goal, it is necessary to improve knowledge about safety, reliability and components’ integrity for more than forty years of operation. In Central and Eastern Europe, the majority of NPPs are VVER types, where some of the components are produced from austenitic steel 08Ch18N10T. Irradiated 08Ch18N10T may exhibit brittle behavior, namely delamination cracks are found in some cases on the fracture surface of irradiated 08Ch18N10T with elongated ?-ferrite. Delamination cracks have also been observed on the fracture surface of high-strength steels or aluminum-lithium alloys. This article presents a state-of-the art review to provide a detailed analysis of the influence of delamination cracks on the toughness of metal alloys. In general, the delamination cracks are present in metal alloys having a high texture and microstructure anisotropy. Three types of delamination cracks have been observed and are classified as crack arrester delamination, crack divider delamination and crack splitting delamination. The microscopy characterization, 3D fracture theories and computational studies explaining possible causes and effects of delamination cracks on the mechanical properties of metal alloys are presented.